The Rollout of Computer Science Education to Every Student in New York City: A Socio-Contextual Social Network Analysis. Issue 11 (November 2020) - Holbert, Nathan; Disalvo, Betsy; Berland, Matthew
Background: CS4All is an $81 million private-public investment aimed at creating the necessary infrastructure to provide computer science experiences to all New York City public-school students by 2025. Purpose: In this paper, we examine the history of the CS4All initiative and document the network of actors and their relationships in the system such that we can understand how this reform is enacted, how it might be reactive to external contexts and pressures, and how the structure and pathways of this particular social network might inform similar efforts elsewhere. Research Design: To structure our analysis of CS4All, we first examine the most recent historic example of a large-scale curricular reform—Man: A Course of Study (MACOS). By reflecting on the network structure of CS4All in light of the design, enactment, and eventual failure of MACOS, we can identify potential pain points and opportunities in CS4All's 10-year effort. We conducted interviews with core members of the CS4All initiative and examined available public records to construct and analyze a social network of key CS4All stakeholders, other actors, processes, and institutions. Conclusions: In our analysis of the CS4All social network, we document how well-connected individuals simultaneously mobilized government resources and grassroots enthusiasm to create the conditions necessary for the initiation of this massive curricular reform effort, and describe the current pathways in place for decision making and resource distribution. Comparing the history and structure of the CS4All initiative to Man: A Course of Study —a failed nationwide curricular reform in the 1960s—we find that CS4All's centralized decision-making process and failure to create and distribute high quality formative assessment tools may lead to challenges to adoption. However, explicit efforts to solicit input from and communicate initiative values to the large diversity of stakeholders throughout NYC, as well as the innovation of a decentralized "buffet-style" curricular approach, may put CS4All on more sure footing.